Life Satisfaction, Pro-Activity, and Employment - Alpaslan Akay; Gökhan Karabulut; Levent Yilmaz (Institute of Labor Economics (IZA), 2021)
Using longitudinal data from the German Socio-Economic Panel (GSOEP), this paper investigates how pro-active time-use (e.g., in sports/arts/socializing) relates to subjective well-being of the unemployed and their probability of finding a new job. Allowing for a variety of socio-demographic and -economic observed characteristics, we find that pro-activity is negatively associated with the well-being loss upon unemployment. That is, the negative unemployment shock on their well-being is mitigated through various stress-reducing activities including, in particular, art participation, socializing, going on trips, and visiting a church. We also find that the probability of returning to the labor market later is positively associated with proactivity during the unemployment period. The results are robust to various checks including estimators, measures, and individual personality characteristics which can correlate with time-use activities.
Keywords: I31; J64; J69; 330; life satisfaction; pro-activity; employment; labor markets